2013
DOI: 10.1097/nen.0b013e3182a31c31
|View full text |Cite
|
Sign up to set email alerts
|

Intact Numbers of Cerebellar Purkinje and Granule Cells in Sudden Infant Death Syndrome

Abstract: Despite much research during recent decades, the etiology and pathogenesis of sudden infant death syndrome (SIDS) remain unknown. Because of the role of the cerebellum in respiratory and cardiovascular control, it has been proposed that it plays an important role in the pathogenesis of SIDS. To date, 5 postmortem studies on the cerebellum of SIDS cases have yielded conflicting results. Using a rigorous design-based stereologic approach, we investigated postmortem cerebella from 9 SIDS patients who died between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 60 publications
2
14
1
Order By: Relevance
“…; Kiessling et al. ) and accordingly, cerebellum pathology is associated with cognitive and behavioral sequeale, as well as mild motor deficits (Patra et al. ; Limperopoulos et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Kiessling et al. ) and accordingly, cerebellum pathology is associated with cognitive and behavioral sequeale, as well as mild motor deficits (Patra et al. ; Limperopoulos et al.…”
Section: Introductionmentioning
confidence: 99%
“…The cerebellum plays a central role for coordination of motor, vestibular, cognitive, and emotional functions (Villanueva 2012) and undergoes significant growth and differentiation during the late fetal and early postnatal period in infants (Dobbing and Sands 1979). It is highly sensitive to environmental factors and postnatal growth restriction after preterm birth (de Kieviet et al 2012;Kiessling et al 2013) and accordingly, cerebellum pathology is associated with cognitive and behavioral sequeale, as well as mild motor deficits (Patra et al 2006;Limperopoulos et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although stereological studies allow for an unbiased approach to tissue sampling, there are real issues of feasibility for stereological studies of the cerebellum, given that the entire cerebellum or even a hemicerebellum are rarely, if ever, available, as is required for such analyses. Indeed, the number of stereological studies of the human cerebellum during the past decade have been limited, and the number of brains examined per study quite limited (4–10 per study group rather than the 50 and 25 per study group in this study) . As an alternative, the nonstereological approach that we used has and continues to be used in numerous other studies, and furthermore, the sample sizes in these studies are considerable (up to 148 subjects in one study) .…”
Section: Discussionmentioning
confidence: 98%
“…Cruz-Sanchez et al (1997) found a delayed maturation of the external granule layer of the cerebellar cortex in SIDS victims, relative to age-matched controls [29]. However, two subsequent studies examining Purkinje cell density and volume in SIDS victims and controls reported no differences [54, 55]. While it is likely that the cerebellar area investigated, as well as methodology issues contribute to variability in these reports, the postmortem control brains used in these studies included those that succumbed from causes known to create hypoxemia prior to death, including strangulation, suffocation, carbon monoxide poisoning, and pneumonia.…”
Section: Discussionmentioning
confidence: 99%